ECOLOGY AND WORLD RELIGIONS - Thottakara, Augustine (Journal of Dharma, 2001)
In recent years ecology has become a very hot and passionate theme of discussion, study and research, not only among academicians, but also among economists, politicians, statesmen, religious leaders and the like, and also in institutions like educational establishments, religious bodies, people's action groups, etc. The study of ecology has got diversified into different branches of learning, like eco-feminism, ecologism, ecosophy/eco-philosophy, eco-theology, eco-spirituality, eco-ethics and so on. We also often hear and read people talking and writing about ecocentrism, eco-dynamics, deep ecology, eco-mind, eco-literature, ecowatch, eco-friendliness, etc. There is a flood of literature, both scientificscholarly and popular-fashionable, in our times on these themes. Most of these works on ecology express deep and genuine concern and alarm about the irreparable damages that are being meted out to the environment and warn that if things do not change for the better, that if man does not take care of this planet now, one day life on it will be miserable and eventually even impossible.